Computational methods in multiphase flow V - International Conference on Computational Methods in Multiphase Flow (5th : 2009 : Wessex Institute of Technology); Mammoli, A. A. (Andrea Alberto); Brebbia, C. A. (Southampton, U.K. ; Boston : WIT Press)
Includes bibliographical references and index